The snow must go on: how German cross-country skiers maintained training and performance in the face of COVID-19 lockdowns - Kock, H.; Schürer, A.; Staunton, C. A.; Hanstock, Helen G. (Frontiers in Sports and Active Living, 2024)
BackgroundThe Covid-19 pandemic in 2020 led to disruption of sporting events, with athletes obliged to comply with national lockdown restrictions.PurposeTo investigate the effect of the Covid-19 pandemic restrictions on national-team XC skiers' annual and weekly training distribution from training diaries, results from submaximal and maximal physiological roller ski tests, and competition results from the International Ski and Snowboard Federation (FIS) world cup.MethodsAnnual and weekly training type (specific, non-specific, strength, other) and intensity distribution (TID) data were collected for 12 German XC-skiers (Tier 4/5; BM: 67 ± 7 kg; age 26 ± 3 years; 6♀: V̇O2max 61.3 ± 3.4 ml · kg · min−1; 6♂: V̇O2max 72.5 ± 6.2 ml · kg · min−1). TID was categorized using a 5-zone scale with Zones 1–2 representative of intensities below the first lactate threshold (LT1), zone 3 between LT1 and LT2, and zones 4–5 above LT2. Training data were grouped by lockdown periods in season 20/21 (L1/L2) and compared to data from the corresponding weeks in 19/20 (C1/C2). Laboratory testing was performed in the general preparation period prior to competition for both seasons. Differences between seasons (C1/C2 vs. L1/L2) in training and performance variables were analysed using repeated-measures ANOVA and linear mixed models.ResultsTotal annual training duration increased by 9% during 20/21 (928 ± 79 h · year−1) compared to 19/20 (852 ± 73 h · year−1). During L1, skiers achieved a greater weekly training duration (mean differences (Δx¯: 7.7 h · week−1) compared to C1, due to an increase in non-specific training (Δx¯: 7.0 h · week−1), whereas L2 resulted in greater weekly training compared with C2 due to a higher specific endurance training volume (Δx¯: 1.4 h · week−1). In 20/21 skiers performed a higher volume of Zone 1 (Δx¯: 149 h · year−1). Laboratory test- and FIS racing performance improved from 19/20 to 20/21.ConclusionGerman XC skiers' training characteristics, laboratory- and racing performance were significantly different between the two seasons. In fact, training duration as well as laboratory- and racing performance increased from 19/20 to 20/21. In spite of seasonal variation in performance and training within an Olympic cycle these findings might suggest that skiers adapted their training effectively to pandemic constraints, ultimately enhancing performance outcomes.